2008 IEEE Computer Society Conference on Computer Vision and Pattern Recognition Workshops 2008
DOI: 10.1109/cvprw.2008.4563166
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of intensity-values acquired by Time-of-Flight-cameras

Abstract: The intensity-images captured by Time-of-Flight (ToF)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…But for the ToF camera, as the primary light source is around the camera, this could still be feasible and should be investigated. Indeed, Stürmer et al [25] observed that the amplitude image in observed an inverse square falloff with distance. Finally, silhouettes constrain the direction of normals of the depth map to be perpendicular to the pixel ray.…”
Section: Choice Of Depth Cuesmentioning
confidence: 98%
“…But for the ToF camera, as the primary light source is around the camera, this could still be feasible and should be investigated. Indeed, Stürmer et al [25] observed that the amplitude image in observed an inverse square falloff with distance. Finally, silhouettes constrain the direction of normals of the depth map to be perpendicular to the pixel ray.…”
Section: Choice Of Depth Cuesmentioning
confidence: 98%
“…We propose to do that using a per-pixel tracking with a Kalman filter as detailed in Section 4.2. Correcting amplitude images using a standardization step [54]. (a) and (b) show the original LR amplitude images for a dynamic scene containing a hand moving towards the camera where the intensity (amplitude) values differ significantly depending on the object distance from the camera.…”
Section: Lateral Registrationmentioning
confidence: 99%
“…Their intensity values differ significantly depending on the camera integration time and on the distance of the scene from the camera; hence, not verifying the optical flow assumption of brightness consistency. Thus, in order to guarantee an accurate registration, it is necessary to apply a standardization step similar to the one proposed in [54] prior to motion estimation, see Fig. 3.…”
Section: Lateral Registrationmentioning
confidence: 99%
“…Again, this is not the case due to pixel gain differences and a radial light attenuation toward the image border. Lindner and Kolb [7] propose a raw value calibration based on work in [9]. The strength and weakness of this class of methods is strongly coupled with the flow method used.…”
Section: Related Workmentioning
confidence: 99%